2022
DOI: 10.1126/scitranslmed.abc1600
|View full text |Cite
|
Sign up to set email alerts
|

Listeria delivers tetanus toxoid protein to pancreatic tumors and induces cancer cell death in mice

Abstract: Pancreatic ductal adenocarcinoma (PDAC) is a highly metastatic disease. Tumors are poorly immunogenic and immunosuppressive, preventing T cell activation in the tumor microenvironment. Here, we present a microbial-based immunotherapeutic treatment for selective delivery of an immunogenic tetanus toxoid protein (TT 856-1313 ) into PDAC tumor cells by attenuated Listeria monocytogenes . This treatment reactivated preexisting TT-specific memory T cells to kill infec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
59
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(62 citation statements)
references
References 78 publications
2
59
1
Order By: Relevance
“…A recent report by Selvanesan et al showed that gemcitabine (GEM) in combination with immunotherapy altered the immunosuppressive TME in a mouse model of PDAC. GEM, which showed to increase ROS production, when combined with the tetanus toxin, decreased the immunosuppression of the PDAC tumor by decreasing the MDSC, and Trges while increasing the CD4 + T cells [ 123 ].…”
Section: Tam Metabolism As a Target For Immunotherapymentioning
confidence: 99%
“…A recent report by Selvanesan et al showed that gemcitabine (GEM) in combination with immunotherapy altered the immunosuppressive TME in a mouse model of PDAC. GEM, which showed to increase ROS production, when combined with the tetanus toxin, decreased the immunosuppression of the PDAC tumor by decreasing the MDSC, and Trges while increasing the CD4 + T cells [ 123 ].…”
Section: Tam Metabolism As a Target For Immunotherapymentioning
confidence: 99%
“…Notably, E. coli ( Michael Schultz, 2008 ; He et al, 2017 ; Christofi et al, 2019 ; Terol et al, 2021 ), Lactobacillus ( Yang et al, 2015 ; Lin et al, 2016 ; Chen et al, 2017 ; Oh et al, 2020 ), Salmonella ( Chirullo et al, 2015 ; Zheng and Min, 2016 ; Li et al, 2017 ; Lim et al, 2017 ; Kawaguchi et al, 2018 ) are the most popular bacteria used as chassis tools for constructing different GEBs. In particular, more than 50 bacterial species, such as Bifidobacterium ( Liu et al, 2018 ), Bacillus subtilis ( Westbrook et al, 2016 ), Listeria monocytogenes ( Selvanesan et al, 2022 ), and Lactobacillus brevis CD2 ( He et al, 2017 ; Alfano et al, 2020 ), are being used in health care and scientific research ( Figure 1 ).…”
Section: Geb In Disease Managementmentioning
confidence: 99%
“…To reform the poorly immunogenic TME of pancreatic ductal adenocarcinoma, Gravekamp et al delivered tetanus toxoid protein, which act as a neoantigen reactivating preexisting memory T cells that were generated during childhood vaccinations, into tumor cells by attenuated Listeria, which could selectively delivered to tumor regions with the help of MDSCs (53). The tetanus toxoid induced attraction of CD4 T cells, with increased production of IFNg, perforin, and granzyme B in the TME, while gemcitabine was used to reduce immune suppression in the TME, which resulted in reduced tumor burden by 80% compared to untreated mice (95).…”
Section: Combined With Chemotherapymentioning
confidence: 99%
“…For certain cancer type with low immunogenicity and low expression of neoantigen such as pancreatic ductal adenocarcinoma, Gravekamp et al has designed a platform to deliver the immunogenic tetanus toxoid protein by L. monocytogenes. In this method, the tetanus toxoid acted as an alternative neoantigen to awaken the preexisting memory T cells generated in childhood vaccination, thus turning the cold TME into a highly immunological environment, which eventually resulted in over 80% reduction of tumor growth and metastasis when coupled with the treatment of gemcitabine (95).…”
Section: Other Types Of Cancersmentioning
confidence: 99%